Functional analysis of mutations in isocitrate dehydrogenase involved in gliomagenesis - Krell, D (2014)
The main subject of my thesis is the investigation of mechanisms of glioma tumorigenesis associated with the recently identified mutations in isocitrate dehydrogenase. Gliomas account for 80% of primary brain cancers. They represent a diverse group of tumours, and are graded from I-IV based on histopathological features. Whilst grade I tumours may be curable with surgery alone, grade II and III gliomas inevitably progress to glioblastoma multiforme (GBM), which is highly resistant to current therapies and carries a very poor prognosis. Despite an improved understanding of the pathways and mechanisms involved in the development of glioma and its progression to grade IV disease, current and novel treatments have so far failed to significantly improve outcome. Isocitrate dehydrogenase (IDH) enzymes catalyse the oxidative decarboxylation of isocitrate to α-ketoglutarate (α-KG). Somatic mutations in genes encoding IDH1 and IDH2 were first identified in glioma and subsequently in acute myeloid leukemia and other solid tumours. These heterozygous point mutations occur at the arginine residue of the enzymes active site and cause both loss of normal enzyme function and gain-of-function, causing the reduction of α-KG to D-2-hydroxyglutarate (D-2HG), which accumulates. D-2HG may act as an oncometabolite through the inhibition of various α-KG dependent enzymes, stimulating angiogenesis, histone modifications and aberrant DNA methylation. Possibly, IDH1/2 mutations may also cause oncogenic effects through dysregulation of the tricarboxylic acid (TCA) cycle, or by increasing susceptibility to oxidative stress. The exact role of mutant IDH1/2 in tumorigenesis however remains unclear. In the work outlined in this thesis, I have demonstrated that the expression of mutant IDH1/2 in glioma cell lines leads to 2-HG accumultation and a reduction in α-KG production and results in HIF1α accumulation and a reduction in 5hmC production. Furthermore, the brain-specific expression of mutant Idh1 in mice also results in 2-HG accumulation and reduced α-KG production, whilst a reduction in 5hmC levels are also seen. This data appears to support the theory that IDH1/2 mutant activity results in the inhibition of α-KG dependent enzymes, either through the accumulation of 2-HG or due to a reduction in α-KG levels. The brain-specific expression of mutant Idh1 in mice also results in increased cellular proliferation and an increase in the expression of the neural stem cell marker, nestin. However gliomas do not develop, perhaps suggesting that additional mutations are required in conjunction with those occuring in IDH1/2 in order to initiate tumourigenesis. Clinically, IDH1/2 mutations may represent a novel therapeutic target in glioma and may also serve as useful diagnostic, prognostic and predictive biomarkers. However, a better understanding of the pathogenesis of mutant IDH is required, to enable effective IDH1/2 directed therapies to be developed in the future.